The Use of Problem-Based Learning Model to Improve Integrated Thematic Learning Outcomes - Bayu Rachman; Setiawan Edi Wibowo; Sekar Purbarini Kawuryan; Melina Maharani; Aprilia, Aprilia; Yogi Aldias Zakariyah (Jurnal Pedagogi dan Pembelajaran, 2025)
Low student motivation and monotonous teaching methods cause integrated thematic learning outcomes to be less than optimal. This study explores the application of the Problem-Based Learning (PBL) model to improve the learning outcomes of grade V students in integrated thematic learning. This study used a quasi-experimental design involving purposively selected participants who were divided into experimental groups taught using PBL and control groups taught conventionally. Data were collected through pretest, posttest, and observation sheet, then analyzed using comparative statistical techniques. The results showed a significant increase in the average score of the experimental group, from 76.7 to 88.33, as well as increased student engagement in the learning process. The study concluded that the PBL model was effective in improving students' understanding, critical thinking ability, and collaboration skills. The findings confirm the potential of PBL as a student-centered learning strategy capable of encouraging active participation and deeper cognitive engagement. This study recommends the wider application of PBL at the basic education level as an effort to improve the quality of learning and develop 21st century competencies.